The Role of Social Media in Digital Marketing in the Creative Industry case study on Aico Creative Indonesia - Sri Mega Wahyuni Arwin; Muhammad Isra; Mutiara Mutiara; Muhammad Aras (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This study explores the role of social media in digital marketing at AicoCreative, a creative agency based in Makassar. Using a qualitative approach, data were collected through in-depth interviews and social media content analysis. The findings reveal that social media plays a crucial role in enhancing brand awareness, increasing audience engagement, and improving the effectiveness of marketing campaigns. Despite challenges such as algorithm changes, AicoCreative has successfully navigated these obstacles through adaptive strategies and in-depth data analysis. The study highlights the importance of flexibility and continuous learning in the ever-evolving digital landscape. Furthermore, the research underscores the value of social media as a powerful tool in building and maintaining a strong online presence, which is essential for sustaining competitive advantage in the creative industry. The insights provided by this study are particularly valuable for other creative agencies aiming to maximize their use of social media in digital marketing efforts. By understanding the strategies employed by AicoCreative, these agencies can better adapt to the dynamic nature of social media and leverage its potential to drive business success.